PENINGKATAN MOTIVASI BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH BERBASIS AUDIO VISUAL PADA SISWA SEKOLAH DASAR - Nur Aviva Zahara; Mohd. Fauziddin; Melvi Lesmana Alim; Iis Aprinawati; Sumianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the application of the audio-visual-based Make a Match type cooperative model can increase student learning motivation in Indonesian language lessons in grade V elementary school.  This research was conducted at SDN 013 Sungai Tarap, Kampa District, Kampar Regency. The form of this research is class action research. This research data was obtained by means of observation. After that the data was analyzed qualitatively. This research was carried out in two cycles, with four stages, namely the planning, implementation, observation, and reflection stages. Based on the results of the research by applying the audio-visual-based Make a Match learning model in Indonesian language lessons can increase student learning motivation. This is because students experience increased motivation by paying attention to each indicator of motivation in learning can be seen in each cycle of meetings. In cycle I, it is known that the level of student learning motivation is only in the “medium” classification with a percentage of only reaching 67%, meaning that it has not reached the expected indicators in this study, and after improvements are made in the second cycle, it increases to the “Very High” classification with a percentage reaching 86.5%.